Protection Of Journalists' Right To Justice From Violence In The Performance Of Their Duties: A Human Rights Perspective - Nadya Andiani, Tara; Riwanto, Agus (International Journal of Educational Research & Social Sciences, 2024)
It is very important to protect the justice rights of journalists in carrying out their duties to maintain freedom of the press and freedom of expression, as well as to prevent intimidation, threats, and violence against journalists in carrying out their journalistic functions.This study uses a normative method with a statutory approach.Overall, the protection of journalists' rights has not met human rights standards in several aspects. Therefore, journalists should join a journalist organization to get help when they face legal problems. Currently, the legal protection received by journalists is still more repressive. One of the things that hinders journalists' organizations in carrying out their duties is that journalists who experience persecution often choose not to pursue the case they have reported to the authorities because they are worried about the consequences they will face if they report or pursue the case to the authorities.